Logistics Management Products, Actors, Technology - Proceedings of the German Academic Association for Business Research, Bremen, 2013 - Dethloff, Jan; Haasis, Hans-Dietrich; Kopfer, Herbert; Kotzab, Herbert; Schönberger, Jörn (Lecture Notes in Logistics,, 2015)
This contributed volume contains the collected research papers presented at the Logistik-Management-Konferenz 2013 organized by the VHB Wissenschaftliche Kommission Logistik, held in Bremen 2013. The papers reflect the current state-of-the-art in logistics and supply chain management, focusing on environmental sustainability in logistics and supply chain network dynamics and control. The target audience primarily comprises research experts in the field as well as practitioners but the book may also be beneficial for graduate students.